Stimulation of Fine Motor Skills in Early Childhood An Intervention Study of Collage Learning Activities - Ferianti, Nurdini; Hidjanah, Hidjanah; Dtakiyyatuddaaimah, Dtakiyyatuddaaimah; Natalia, Natalia (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2025)
This study aims to stimulate the fine motor skills of grade B children of Aisyiyah 01 Leuwiliang Kindergarten through collage learning activities. The type of research used is classroom action research (CAR). This study consists of two cycles and each cycle is carried out five meetings. The subjects of this study were 12 children aged 5-6 years consisting of 12 boys. Data collection techniques consisted of observation and documentation. The instruments used in this study were daily learning implementation plans (RPPH), field notes. Data analysis techniques were carried out descriptively, qualitatively and quantitatively. The indicator of success of this study is if the calculation of the overall percentage of children shows 71% or more, then the child has increased fine motor skills. The results of the research that have been conducted by researchers show that stimulation of children's fine motor skills through collage learning activities has a positive change. This can be seen from the increase in the percentage of the average value at the end of the cycle. Pre-cycle children showed motor skills of 40%, namely the level of development achievement has not developed. While in cycle 1 it reached 59% and in cycle 2 it reached 85%.